Public perceptions of expert disagreement: Bias and incompetence or a complex and random world?. (April 2017) - Dieckmann, Nathan F.; Johnson, Branden B.; Gregory, Robin; Mayorga, Marcus; Han, Paul K. J.; Slovic, Paul
Expert disputes can present laypeople with several challenges including trying to understand why such disputes occur. In an online survey of the US public, we used a psychometric approach to elicit perceptions of expert disputes for 56 forecasts sampled from seven domains. People with low education, or with low self-reported topic knowledge, were most likely to attribute disputes to expert incompetence. People with higher self-reported knowledge tended to attribute disputes to expert bias due to financial or ideological reasons. The more highly educated and cognitively able were most likely to attribute disputes to natural factors, such as the irreducible complexity and randomness of the phenomenon. Our results show that laypeople tend to use coherent—albeit potentially overly narrow—attributions to make sense of expert disputes and that these explanations vary across different segments of the population. We highlight several important implications for scientists, risk managers, and decision makers.